Analisis Analyzing Banks’ Efficiency in Distributing Credit (Loans) Using Data Envelopment Analysis (DEA) Method - Dewi, Putu Ayu Padma; Ismail, Munawar (Contemporary Studies in Economic, Finance and Banking, 2025)
Abstract: The aim of this research is to measure the efficiency of conventional commercial banks in distributing credit in the 2018 – 2022 period using the DEA method. For this study, 42 Indonesian conventional commercial banks serve as the analytic unit. The input variables used consist of Third Party Funds and labor costs, while the output variables consist of credit and interest income. The results of this research indicate that Indonesia's traditional commercial banks are currently not operating efficiently. Of the 42 banks examined throughout the five-year research period, just nine of them attained a 100% efficiency level. To reach a 100% efficiency value, inefficient banks can increase their output or decrease their input.